Micro Business Empowerment Model Through Cash Waqf - Agus Suaidi Hasan; Sri Herianingrum (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
Poverty and economic inequality have become persistent problems. It is believed that this problem can be faced with cooperation and mutual concern. Through this, Islam as a holistic teaching has actually provided a means of solution to dealing with this problem, namely the existence of Islamic philanthropy in the form of zakat, infaq, shadaqah and waqf. Especially in the field of waqf, it has now experienced a development of meaning, where currently the practice of waqf with money or cash waqf has developed. The existence of waqf money is a huge potential, especially in Indonesia as the largest Muslim country in the world. With this potential, it is hoped that the management of waqf money can become a new alternative in economic development, especially as an alternative financing for empowering micro businesses. This research uses a qualitative approach with literature study method, data is obtained from electronic media, books, and journals. The result of this research is to develop a sharia financing model through cash waqf instrument as an alternative source of financing and empowerment of micro businesses.Keywords: Cash Waqf, Sharia Financing, Empowerment, Micro Business